A micro-financing option the "Bombay" as informal money lender in Iloilo City - Fedoc, Maricel; Lava, Althea; Nam, Ju-hyun; Palec, Jeszel Marie; Remedios, Joemarie
A major constraint to the participation and contribution of poor and vulnerable households in economic growth is access to financial credit. It has been estimated that more than 500 million people worldwide need access to financial services. However, formal financial intermediaries such as commercial banks often do not serve poor households for reasons that include the lack of traditional collateral, high costs of small transactions, and geographic isolation. As a developing country, the Philippines has a large informal sector comprised of micro-enterprises. Many of these are severely resource-constrained small vendors, whose survival in business relies heavily on access to financing. This usually comes from the informal sector as well in the form of informal micro-financiers called "5-6." Two types of 5-6 financiers are found in the Philippines, each with a distinctive lending mechanism, Filipinos and Indians better known as the Bombays. The 5-6 system has helped finance many micro-entrepreneurs or would -be micro-entrepreneurs to start up their business. Despite this illegal or informal means of gaining fast money, Filipinos from both the margenalized sectors and middle class still engage in it and may benefit from it, although these sectors are very susceptible to economic downs. India's money, the system's funds source, is somewhat injected into the Philippine economy through financing these micro-enterprises. Given the importance of the infrmal lending sector, there is a need to look into the environment that depicts the informal money lending business of the Bombay, being one of the factors that help improve Philippine's economic status. It would be interesting to know the lending practices these people observe, reasons of borrowers and lenders for engaging in informal money lending as well as the potential problems they encounter. This study aims to describe the environment of informal money lending in the case of Bombays in Iloilo City. Specifically, it aims to describe the informal money lender's socio-demographic characteristics and economic profile, determine their reasons for engaging in informal money lending, identify the potential problems they encounter in lending and their solutions to these problems encountered; identify informal money lending practices and be able to describe the informal money lending environment; due to describe the socio-demographic and economic profile of informal money lending borrowers, identify their reasons for borrowing from Bombays; determine their advantages and disadvantages in lending from Bombays, identify potential problems they encounter and their solutions to the problems encountered. The study focuses on the Bombays as informal money lenders and their lending operations in Iloilo City. It includes their socio-demographic characteristics, reasons for engaging in informal lending, problems encountered in lending, and solutions to such problems. the study also covers the Bombays' informal money practices specifically average amount loaned to borrowers, interest rates, terms of payment, methods of collection, penalties for nonpayment of loan, form of credibility check and terms of renewal of loans. Furthermore, the study looks into the characteristics of the borrowers, their reasons for engaging in informal money lending, the advantages and disadvantages they experience in borrowing from the Bombay, and problems they encounter in borrowing from the Bombays and solutions to such problems. The result of the study provides knowledge on the emergence of informal money lenders in Iloilo City, specifically the Bombay. It leads to a better understanding of the factors that encouraged small business owners, especially tiangge owners, to operate through the financial assistance of informal money lending Bombays, and give a brief description of these micro-entrepreneurs' needs in financing that banks and other formal lending institutions cannot provide. The study also brings to light the significance of the role of informal money lending to Ilonggos. The study also provide reasons behind the continuing support of the Ilonggos on informal money lending operations, and the benefits that it may bring to Ilonggo entrepreneurs and their businesses. The descriptive research design was used in this study. It describes the situation or state of affairs in an informal money lending system of the Bombays, the condition of the system as well as the characteristics of the lenders and borrowers. Convenience sampling was used in selecting respondents from among the Bombays lenders. Whoever was available at the time of the interview was selected as respondent of the study. In the case of the borrowers, multi-stage sampling was used in identifying respondents from the borrowers. The districts of Mandurriao, Jaro and City Proper were chosen purposely since these districts are known to be the areas where most of the borrowers are located. The researcher used questionnaire and interview schedules in the collection of primary data. Questionnaires were used for borrowers and interview schedules for lenders. Data obtained from questionnaires and interviews was analyzed using frequency and percentages. The questionnaires was used as interview schedule for the respondents among the borrowers...